Time for Kenny - Pinkney, J. Brian (Greenwillow Books, an imprint of HarperCollinsPublishers, 2021)
During his busy day, Kenny gets dressed, fights his fear of the vacuum cleaner, gets a soccer lesson from his sister, and prepares for bed, with his loving family always near.